LINC00885 a Novel Oncogenic Long Non-Coding RNA Associated with Early Stage Breast Cancer Progression - Abba, Martín Carlos (2020)
Long intergenic non-protein coding RNA 885 (LINC00885) was identified as significantly upregulated in breast ductal carcinoma in situ (DCIS). The aim of this study was to characterize the phenotypic e ects and signaling pathways modulated by LINC00885 in non-invasive and invasive breast cancer models. We determined that LINC00885 induces premalignant phenotypic changes by increasing cell proliferation, motility, migration and altering 3D growth in normal and DCIS breast cell lines. Transcriptomic studies (RNA-seq) identified the main signaling pathways modulated by LINC00885, which include bioprocesses related to TP53 signaling pathway and proliferative signatures such as activation of EREG, EGFR and FOXM1 pathways. LINC00885 silencing in breast cancer lines overexpressing this lncRNA leads to downregulation of proliferation related transcripts such as EREG, CMYC, CCND1 and to significant decrease in cell migration and motility. TCGA-BRCA data analyses show an association between high LINC00885 expression and worse overall survival in patients with primary invasive breast carcinomas (p = 0.024), suggesting that the pro-tumorigenic e ects of LINC00885 overexpression persist post-invasion. We conclude that LINC00885 behaves as a positive regulator of cell growth both in normal and DCIS breast cells possibly operating as a ceRNA and representing a novel oncogenic lncRNA associated with early stage breast cancer progression.